2018
DOI: 10.1186/s40880-018-0307-y
|View full text |Cite
|
Sign up to set email alerts
|

NS1‐binding protein radiosensitizes esophageal squamous cell carcinoma by transcriptionally suppressing c‐Myc

Abstract: BackgroundCisplatin-based chemotherapy with concurrent radiotherapy is a standard treatment for advanced esophageal squamous cell carcinoma (ESCC). NS1-binding protein (NS1-BP), a member of the BTB-kelch protein family, has been shown to inhibit the proliferation of Hela cells by suppressing c-Myc. In the present study, we examined the potential function role of NS1-BP expression in ESCC, and particularly, the sensitivity of ESCC to radiotherapy.MethodsNS1-BP expression was examined using immunohistochemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 47 publications
2
14
0
2
Order By: Relevance
“…In addition, the results of the cell cycle analysis demonstrated that MSI1 suppression induced cell cycle arrest, which is considered to be an important factor in regulating cancer progression. Our findings were in agreement with those of previous studies on other types of tumors (26,27).…”
Section: Discussionsupporting
confidence: 94%
“…In addition, the results of the cell cycle analysis demonstrated that MSI1 suppression induced cell cycle arrest, which is considered to be an important factor in regulating cancer progression. Our findings were in agreement with those of previous studies on other types of tumors (26,27).…”
Section: Discussionsupporting
confidence: 94%
“…Esophageal cancer (EC) is the eighth most common cancer type and the sixth leading cause of cancer death worldwide [1]. It mainly includes esophageal squamous cell carcinoma (ESCC) and esophageal adenocarcinoma (EAC) [2].…”
Section: Introductionmentioning
confidence: 99%
“…miR-145-5p also inhibited cell growth and invasion and attenuated circDUSP16-induced tumor-promoting effects in GC cells. It was shown that NS1-Binding Protein (NS1-BP) is implicated in c-Myc transcriptional control [32] and facilitates the radio-sensitivity by inhibiting c-Myc in esophageal squamous cell carcinoma [33]. We found that influenza virus NS1A-binding protein (IVNS1ABP) was a direct target of miR-145-5p and miR-145-5p reduced circDUSP16-induced IVNS1ABP expression in GC cells.…”
Section: Discussionmentioning
confidence: 88%